KARAKTRISTIK PERPINDAHAN PANAS DA PENURUNAN TEKANAN PIN FIN OBONG INOVATIF PADA TRAILING EDGE BLADE TURBIN GAS - Baskoro, Punto (2016)
This research evaluates a pin-fins cooling performance of gas turbine blade. The aim is to investigate computationally the heat transfer coefficient (HTC) and friction factor (f) along the cooling passage. By using k-epsilon turbulence model, numerical investigations were performed at two steps: first, to validate simulation results from an existing circular pin-fin cooling with staggered arrays against experimental measurement. Seven types structured mesh from coarse (Δy+ = 48.84) to fine (Δy+ = 1.21) were evaluated during this step; second, to understand the oblong pin-fins cooling performance on various angle orientation. Simulations were performed by keeping the same initials and boundary conditions as the experiment, and varying Reynolds number from 9,000 to 36,000. The result demonstrates that validation can be considered acceptable by developing mesh up to 1.6 million elements with fine resolution (Δy+ = 1.21). The expansion factor is a key important factor in order to control grid quality resolution near wall regions. CFD predicted HTC and pressure loss are in good agreement with available experimental data, even though it is found over-prediction data after the second pin-fin row in the HTC simulation. Investigation of three different oblong pin-fins cooling (GN1, GN2 and GN4) shows that the HTC of pin-fin GN2 is the greatest level compared to other configurations. The HTC of pin-fins surface increases moderately along the cooling passage due to the increase of flow turbulence that caused by contraction channel and increasing Reynolds number. In contrast, the friction factor decreases gradually along the cooling passage. The HTC of pin-fins GN2 is about twice the HTC of the baseline model (G2.5).